The effect of the COVID-19 pandemic on the mental health of obstetrics and gynaecology trainees: a world-wide literature review - G. Ganeshan; H. Sekar; S. Reilly; C. Kuo; S. Singh; J. Michaels; W. Yoong (Journal of Obstetrics and Gynaecology)
Background Coronavirus (COVID-19) pandemic has affected the training and wellbeing of obstetrics and gynaecology (O&G) trainees. The aim of this review is to offer a worldwide overview on its’ impact on the mental health of O&G trainees, so that measures can be put into place to better support trainees during the transition back to the ‘new normal’.Methods Key search terms used on PubMed and Google Scholar databases include: mental health, COVID-19, O&G, trainees, residents.Results Fifteen articles (cumulative number of respondents = 3230) were identified, of which eight employed validated questionnaires (n = 1807 respondents), while non-validated questionnaires were used in seven (n = 1423 respondents). Studies showed that COVID-19 appeared to exert more of a negative impact on females and on senior trainees’ mental health, while protective factors included marriage/partner and having had children. Validated and non-validated questionnaires suggested that trainees were exposed to high levels of anxiety and depression. Their mental health was also affected by insomnia, stress, burnout and fear of passing on the virus.Discussion This review analyses the global impact of COVID-19 on O&G trainees’ mental health, showing a pervasive negative effect linked to fear of the virus. Limited psychological support has led to prolonged issues, hindering patient safety and increasing sick leave. The study underscores the urgency of comprehensive support, particularly in female-dominated fields. Addressing these challenges is crucial for future pandemics, highlighting the need to learn from past mistakes and prioritise mental health resources for trainee well-being during and beyond pandemics.